Pengaruh Pengalaman Kerja, Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Asuka Engineering Indonesia - Muhammad Royyan Ivan Purnawan; Roziana Ainul Hidayati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Background - In 2017 employee performance did not reach the target due to lack of work experience, motivation and a work environment that was less supportive of employee performance, however in the following year the realization of employee performance began to increase due to the influence of work experience, the form of motivation provided by the company to employees and the work environment. focused and more conducive. So that from 2018 to 2021 there will be an increase in employee performance due to the influence of work experience, motivation and a good work environment. Objective - This study aims to test the Effect of Work Experience, Motivation, and Work Environment on Employee Performance of PT Asuka Engineering Indonesia. Design/Methodology/Approach - This research is quantitative research. The number of samples used in this research was 50 respondents. The analysis technique for testing hypotheses uses the Statistical Package for the Social Sciences (SPSS). Findings - In this research there is a positive and significant influence between Work Experience (X1) and Employee Performance (Y). There is a positive and significant influence between Work Motivation (X2) and Employee Performance (Y). There is a positive and significant influence between the Work Environment (X3) and Employee Performance (Y). Research implications - Based on the results of the research conducted, it can be concluded that the work experience variable has a positive and significant effect on employee performance. The positive meaning is that the more work experience an employee has, the better the employee's performance. From the results of the t test which shows that the sig value of 0.009 <0.05 is said to be significant, which means that work experience can be a factor and can improve the performance of PT employees. Asuka Engineering Indonesia. Based on the results of the research conducted, it can be concluded that the work motivation variable has a positive and significant effect on employee performance. The positive meaning is that the better the work motivation given to employees, the better the employee's performance. From the results of the t test which shows that the sig value of 0.001 < 0.05 is said to be significant, which means that work motivation can be a factor and can improve the performance of PT employees. Asuka Engineering Indonesia. Based on the results of the research conducted, it can be concluded that work environment variables have a positive and significant effect on employee performance. The positive meaning shows that the better the work environment, the better the employee's performance. From the results of the t test which shows that the sig value of 0.015 <0.05 is said to be significant, which means that the work environment can be a factor and can improve the performance of PT employees. Asuka Engineering Indonesia. Research limitations - This research was only conducted on employees of PT. Asuka Engineering Indonesia.